2015
DOI: 10.1371/journal.pone.0131743
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Activates Hepatitis B Virus Replication by Elevation of p21 (Waf1/Cip1) and C/EBPα Expression

Abstract: Hepatitis B virus reactivation is an important medical issue in cancer patients who undergo systemic chemotherapy. Up to half of CHB carriers receiving chemotherapy develop hepatitis and among these cases a notable proportion are associated with HBV reactivation. However, the molecular mechanism(s) through which various chemotherapeutic agents induce HBV reactivation is not yet fully understood. In this study, we investigated the role of the cell cycle regulator p21 (Waf1/Cip1) in the modulation of HBV replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The precise mechanisms of HBV reactivation upon administration of different agents remain largely unknown, but has been linked either to the impairment of immune responses (TNF-α inhibitors, B-cell depleting agents, chemokine and integrin inhibitors, kinase inhibitors, proteasome inhibitors) or activation of transcription of HBV covalently closed circular DNA (cccDNA) (histone deacetylase inhibitors) [5]. Several lines of evidence indicate that HBV reactivation may be related to oxidative stress, DNA damage/DNA damage response and interconnected alterations in the intracellular signaling and cell cycle progression in the infected cells [9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanisms of HBV reactivation upon administration of different agents remain largely unknown, but has been linked either to the impairment of immune responses (TNF-α inhibitors, B-cell depleting agents, chemokine and integrin inhibitors, kinase inhibitors, proteasome inhibitors) or activation of transcription of HBV covalently closed circular DNA (cccDNA) (histone deacetylase inhibitors) [5]. Several lines of evidence indicate that HBV reactivation may be related to oxidative stress, DNA damage/DNA damage response and interconnected alterations in the intracellular signaling and cell cycle progression in the infected cells [9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…HDACi-induced G1/S phase arrest might contribute to de novo HBV replication before cells enter into mitosis, and regulation of some transcriptional factors which are involved in cell growth and differentiation, such as E2F transcription factor 5, CCAAT/enhancer-binding protein α (C/EBPα), hepatocyte nuclear factor 4 alpha, etc. 39 Increased p21 has been shown to recruit C/EBPα to the HBV promoter after doxorubicin treatment; 40 thus, FK228/SAHA-induced elevated p21/p27 expression might stimulate HBV replication by increasing the recruitment of C/EBPα or other transcriptional factors to HBV promoters. In addition, HDACi treatment has been reported to induce the depletion of uracil DNA glycosylase, which can counteract APOBEC3-induced hypermutations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that doxorubicin and other chemotherapeutic medications enhanced HBV replication in HBV-expressing hepatoma cells 18 . Doxorubicin induced P21(Waf1/Cip1) expression and enhanced the binding of CCAAT/enhancer-binding protein α to the HBV core promoter, thereby contributing to enhanced HBV replication 28 Recently, Mouler Rechtman M et al . reported that anticancer cytotoxic agents induce PGC-1α upregulation and coactivate HBV transcription 29 .…”
Section: Discussionmentioning
confidence: 99%